The Criminalization of Environmental Harm: Theoretical Perspectives in the European Union - Krisztina Ficsor (Universitas Islam Indonesia, 2024)
Climate change poses a serious threat to the health and well-being of people and the environment and is one of the most pressing issues facing the European Union today. The damage caused by rising global temperatures, extreme weather events, and the resulting environmental degradation are not only ecological concerns but also directly impact human life. The greatest challenge for states worldwide is to find out how to combat climate change and its consequences with legislation. This situation demands a reevaluation of legal liability in the context of environmental harm. Traditional legal approaches often focus on punishing individual transgressions and direct harm, but climate change and environmental damage are collective and long-term problems that require a more systemic approach. The complexity of the problem comes from the fact that climate change and its serious consequences are the result of human action. However, most of these actions are legal. The special features of environmental harm and damage must encourage governments to reconsider the concept of legal liability and other general issues concerning the function of law. With normative legal methodology, this essay elaborates on these issues from the perspective of European Criminal Law and the criminalization of environmental harm.